A educação das emoções, do desejo e do prazer na Ética a Nicômacos de Aristóteles - Berra, Eliane Aparecida (2018)
This dissertation deals with the education of emotions, desire and pleasure in Aristotle's Nicomachus Ethics, in order to investigate what is the basis of this education. The hypothesis defended is that the habit in Aristotle is the fundamental element to concretize the education of the emotions, the desire and the pleasure aiming at the virtuous act. The methodology used in the development of the study is of bibliographic nature and follows the analytic reconstructive procedure, which seeks to develop the main concepts of the Aristotelian work and its commentators on the theme of education of emotions, desire and pleasure. The dissertation consists of two chapters. The first, articulating key concepts of ethics, presents the relation between anthropology and moral virtue as the basis in the conception of education of emotions, desire and pleasure in Aristotle. The second chapter discusses the education of emotions, desire, and pleasure, in order to understand how reason can govern them in order to ensure that virtuous action is affected. It analyzes how reason can act in the command of desire and how it can educate it by the habit of well-wish, having as principle the right desire that understands the good as good in itself. Based on the concepts of the philosopher, it is concluded that the education of emotions, desire and pleasure is possible when rationality is preponderant, since it can make the agent to reflect in order to orient his impulses, acting in an intelligent way, observing the laws and directing properly the emotions, the desire and the pleasure. Through the control of reason, habit is established and constitutes the government of emotions, desire and pleasure for having mediated a correct education. Habit, according to Aristotle, to be rooted requires time, in order to be properly cultivated and to constitute moral virtue. The virtuous in Aristotle has the educated desire, and for this reason he knows how to take pleasure in what one should act, when one should act and how one should act. Thus Aristotle's habit is established as the basis for the education of emotions, desire, and pleasure, for through the command of reason it was acquired in a way that was firmly rooted, constituting the government of emotions, of desire, and of pleasure. Consequently, the education of emotions, desire, and pleasure is firmly realized through good habits acquired and rooted from an early age.